Desain Antena Mikrostrip Segitiga Terpancung Tunggal LHCP Patch Stack sebagai Basic Sensor CP-SAR - Muhammad Fauzan Edy Purnomo; Vita Kusumasari; Rini Nur Hasanah; Hadi Suyono (Program Studi Teknik Elektro S1 ITN Malang, 2020)
The development of SAR radar technology (Synthetic Aperture Radar) and aircraft as the carrier media is relatively fast and demands the need for communication facilities and infrastructure that have a variety of platforms and high-quality imaging, which can produce processed data with high resolution and good images for all type explored terrain. Based on the demands of the progress of civilization, the antenna placed on the carrier media should have simple, compact, thin, and conformal characteristics. This research will analyze and study the need for a single, low power microstrip antenna in the L-band (1.25 GHz - 1.27 GHz) for CP (Circularly Polarized)-SAR radar applications. The use of Method of Moments (MoM) show that the result of characteristic performance and S-parameter for the single triangular truncated patch stack Left-Handed Circular Polarization (LHCP) antenna, f = 1.25 GHz, are consecutively 7.23 dBic of gain, 0.51 of axial ratio, -16.35 dB of S-parameter. Moreover, the 3-dB axial ratio bandwidth LHCP antenna is around 15 MHz or the percentage around 1.2% Perkembangan teknologi radar SAR (Synthetic Aperture Radar) dan pesawat terbang sebagai media pembawanya relatif cepat dan menuntut kebutuhan sarana dan prasarana komunikasi yang memiliki ragam platform dan pencitraan yang berkualitas tinggi, yang mampu menghasilkan data olahan dengan resolusi tinggi dan gambar yang baik untuk segala jenis medan yang dijelajahi. Berdasarkan tuntutan kemajuan peradaban zaman, maka antena yang diletakan pada media pembawa tersebut, seyogyanya memiliki karakteristik sederhana, compact, tipis, dan conformal. Dalam makalah ini akan dianalisis dan dikaji kebutuhan antena mikrostrip tunggal berdaya rendah pada pita L (1,25 GHz - 1,27 GHz) untuk aplikasi radar CP (Circularly Polarized)-SAR. Penggunaan Method of Moments (MoM) menunjukkan bahwa hasil performansi karakteristik dan S-parameter untuk antena segitiga terpancung tunggal Left-Handed Circular Polarization (LHCP) patch stack, f = 1.25 GHz, berturut-turut yaitu gain sebesar 7.23 dBic, axial ratio sebesar 0.51, dan S-parameter sebesar -16.35 dB. Selain itu, bandwidth axial ratio 3-dB antena LHCP sekitar 15 MHz atau persentasinya sebesar 1,2%.